Sustainable manufacturing practices and climate considerations – a study of stakeholders views - Penubarthi, Venkata Subbu Kalyan (2022)
Ecological and environmental impact caused by manufacturing firms supporting better living standards and growing population needs, is getting noticeable attention from several stakeholders. Stakeholders to an organization, both Internal and external are becoming more vigilant of impact to climate change; In particular, those external to the organization, like non-governmental organizations (NGO’s), institutional players like government or professional bodies, continue to engage in discussions that drive better reporting of results from business processes that impact climate change like carbon footprint, greenhouse gas emissions, waste management, water and other resources consumption. Those internal to the organization are working towards meeting the expectations set by governments or drive business processes that bring more profits to their firm. Effective engagement of stakeholders at different levels is required to respond to accelerating impact to climate change. Level of influence exercised by stakeholders differs by category and it is important to understand the level of engagement they show on sustainable manufacturing practices, factoring in climate considerations and identify shortcomings that need to be addressed, to bring better collaboration between stakeholders and the firm with respect to climate considerations. Objective of this study is to identify level of awareness that stakeholders have on sustainable manufacturing practices, level of importance they give during their decision making and varying degree of importance given by different stakeholders. The recommendations are provided based on extensive literature reviewed and insights collected from data analysis. Manufacturing entities in India should make conscious efforts to effectively collaborate with its stakeholders, in particular suppliers and continue to share knowledge, information that can enhance business processes and drive towards sustainability in manufacturing practices being followed at both the ends. Further, professional bodies like RBI and Sovereign bodies (state and central governments) should define meaningful incentive / rewards system that is tied to the positive climate considerations factored into by manufacturing entities and encourage them towards better compliance, improvements.